http://img263.imageshack.us/img263/5338/70679125.png

Hi guys,

May I confirm if my approach is correct so far as I work towards the solution.

I apologize in advance, it looks a bit long, but it is just the first few steps of the approach (no work on equating coefficients etc yet)

1) This ODE has a regular singular point at x=0 and so Frobenius Method is used where

$\displaystyle y=\sum_{n=0}^{\infty}a_{n}x^{n+s}$?

2) If 1) is correct, when I try to write it out as a series I obtain 3 series:

$\displaystyle x \sum_{n=0}^{\infty} (n+s-1)(n+s)a_{n}x^{n+s-2} - 2 \sum_{n=0}^{\infty} (n+s)a_{n}x^{n+s-1} + 9x^5 \sum_{n=0}^{\infty} a_{n}x^{n+s} &= 0 $

Which simplifies to:

$\displaystyle \sum_{n=0}^{\infty} (n+s-1)(n+s)a_{n}x^{n+s-1} - \sum_{n=0}^{\infty} 2(n+s)a_{n}x^{n+s-1} + \sum_{n=0}^{\infty} 9a_{n}x^{n+s+5} &= 0$

May I confirm if this is correct?

3) My next question is that I attempt to make the summation indexes the same - i.e. n=5. However I get a large number of terms that need to be taken out of the first 2 series - so wanted to confirm if my approach is correct in the first place.

Thank you for any feedback given

Linda